Preparation method of positive electrode material, positive electrode material and lithium-sulfur battery

The metal catalyst is filled by the negative pressure liquid phase method and a carbon nanotube-coated metal particle structure is formed, which solves the problems of low utilization rate of active substances and catalyst stability in lithium-sulfur batteries, and improves the capacity and cycle stability of the battery.

CN119297247AActive Publication Date: 2025-01-10TSINGHUA SHENZHEN INTERNATIONAL GRADUATE SCHOOL
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411459329.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-10
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Due to the insulating materials, lithium sulfur batteries have low utilization rate of active substances, and the dissolution and corrosion of lithium polysulfide caused by the charging and discharging process. The amount of existing catalysts is too large and easily toxic and has too strong adsorption.

Method used

The negative pressure liquid phase method is used to fill the inside of the carbon nanotube, convert it into metal particles through heat treatment, and recombinate it with the carbon nanotube to form a carbon nanotube covered with metal particles structure, reducing the direct contact between the catalyst and polysulfide, and improving the Catalytic activity and stability.

Benefits of technology

The catalyst usage is reduced, the capacity and cycle stability of lithium-sulfur batteries are improved, the shuttle effect is reduced, and the sulfur utilization rate and the long-term effectiveness of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297247A_ABST
    Figure CN119297247A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a positive electrode material, the positive electrode material and a lithium-sulfur battery, and the preparation method of the positive electrode material comprises the following steps: pretreating a carbon nanotube to obtain an open carbon nanotube; the method comprises the following steps: putting an open carbon nanotube into a container, and vacuumizing the container until the vacuum degree is 0.05-0.1 Pa; keeping the vacuum degree, and injecting a metal catalyst solution into the container to soak the open carbon nanotubes to obtain a precursor mixture; the precursor mixture is dried and subjected to heat treatment, the metal catalyst is converted into metal particles, the opening carbon nanotubes are filled with the metal particles, and a carbon nanotube composite material is obtained; and adding sulfur into the carbon nanotube composite material, grinding and heating to obtain the positive electrode material. According to the present invention, the metal catalyst is efficiently coated with the carbon nano-tube through the negative pressure liquid phase method, such that the catalytic activity and the stability of the catalyst are improved, the shuttle effect in the lithium-sulfur battery is reduced, and the long-term effect and the stability of the positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of positive electrode materials, and in particular to a method for preparing a positive electrode material, a positive electrode material, and a lithium-sulfur battery. Background Art

[0002] As the global demand for renewable energy and electric vehicles continues to increase, traditional lithium-ion batteries face the dual challenges of energy density and cost. Lithium-sulfur batteries have become a hot topic of current research due to their high theoretical capacity, high energy density and low cost. Lithium-sulfur batteries use sulfur as the positive electrode material. Compared with cobalt and nickel in traditional lithium-ion batteries, sulfur is abundant in resources and low in cost, which helps reduce dependence on rare metals and impact on the environment.

[0003] However, based on the inherent reaction mechanism of lithium-sulfur batteries, lithium-sulfur batteries currently have the following problems: First, due to the S8 (5×10 -30 S cm -1 ) and Li2S (3.6×10 -7 S cm -1 ) has poor insulation, resulting in low utilization of active materials during the charge and discharge process. Secondly, the lithium polysulfide produced during the charge and discharge process dissolves in the electrolyte, and a "shuttle effect" occurs between the positive and negative electrodes, resulting in a large loss of active materials, rapid capacity decay, and corrosion of the lithium negative electrode. Introducing catalysts is an effective strategy to solve the above problems, but the catalysts currently used in lithium-sulfur batteries have problems such as excessive catalyst dosage, poisoning of the catalyst and polysulfide reaction, and excessive adsorption of polysulfide. Summary of the invention

[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a method for preparing a positive electrode material.

[0005] In addition, the embodiments of the present application also provide a positive electrode material prepared by the aforementioned preparation method and a lithium-sulfur battery using the positive electrode material.

[0006] The present invention provides a method for preparing a positive electrode material, which comprises the following steps: pre-treating the carbon nanotubes to obtain open carbon nanotubes; Placing the open carbon nanotubes in a container, and evacuating the container to a vacuum degree of 0.05 Pa to 0.1 Pa; Maintaining the vacuum degree, injecting a metal catalyst solution into the container to impregnate the open carbon nanotubes to obtain a precursor mixture; Drying and heat-treating the precursor mixture to convert the metal catalyst into metal particles and fill the metal particles inside the open carbon nanotubes to obtain a carbon nanotube composite material; and Sulfur is added to the carbon nanotube composite material, and the mixture is ground and heated to obtain the positive electrode material.

[0007] In some possible embodiments, the carbon nanotubes are oriented carbon nanotubes, and the oriented carbon nanotubes include at least one of carbon nanotube arrays, oriented multi-walled carbon nanotubes, and oriented double-walled carbon nanotubes; and / or The purity of the carbon nanotubes is lower than 99%.

[0008] In some possible embodiments, the metal catalyst solution includes at least one of CoCl2, Co(NO3)2, FeCl3, Fe(NO3)3, NiCl3, Ni(NO3)3, ZnCl2 and Zn(NO3)2; and / or The concentration of the metal catalyst solution is 1 g / L to 5 g / L.

[0009] In some possible embodiments, in the precursor mixture, the mass ratio of the metal catalyst solution to the open carbon nanotubes is (0.1-0.5):1.

[0010] In some possible embodiments, the step of impregnating the open carbon nanotubes with the metal catalyst solution further includes: The metal catalyst solution and the open carbon nanotubes are stirred for 3 hours to 5 hours.

[0011] In some possible embodiments, when the container is evacuated, the temperature inside the container is 60° C. to 80° C.

[0012] In some possible embodiments, in the heat treatment step, the heat treatment temperature is 400° C. to 800° C., and the heat treatment time is 3 h to 5 h.

[0013] The present application provides a positive electrode material, which is prepared by the above-mentioned positive electrode material preparation method. The positive electrode material includes a carbon nanotube composite material and sulfur loaded on the carbon nanotube composite material, wherein the carbon nanotube composite material includes open carbon nanotubes and metal particles located inside the open carbon nanotubes.

[0014] An embodiment of the present application also provides a lithium-sulfur battery, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the separator is arranged between the positive electrode plate and the negative electrode plate, and the positive electrode plate includes the aforementioned positive electrode material.

[0015] Compared with the prior art, the preparation method of the positive electrode material provided in the embodiment of the present application can quickly introduce the metal catalyst solution into the interior of the carbon nanotubes by utilizing the liquid phase negative pressure filling technology under a certain vacuum degree, and then convert the internal metal catalyst into metal particles through subsequent heat treatment, thereby finally obtaining the positive electrode material in which the metal particles are coated inside the carbon nanotubes.

[0016] The positive electrode material provided by the embodiment of the present application has a metal catalyst coated inside the carbon nanotube, which reduces the direct contact between the polysulfide generated by the positive electrode material when used in the lithium-sulfur battery reaction and the metal catalyst, resulting in the metal catalyst being sulfided and losing its catalytic activity, thereby improving the stability and catalytic activity of the metal catalyst, thereby helping to reduce the amount of metal particle catalyst used; at the same time, the barrier effect of the carbon nanotube weakens the strong adsorption effect between the metal particle catalyst and the polysulfide, releasing the active catalytic sites of the metal particle catalyst, which is conducive to improving the efficiency of the catalytic reaction, effectively adsorbing and rapidly catalytically converting polysulfide, thereby reducing the shuttle effect in the lithium-sulfur battery. In addition, the composite of the metal particle catalyst and the carbon nanotube establishes an effective conductive skeleton, improves the conductivity of the positive electrode material and the sulfur utilization rate, thereby improving the capacity of the lithium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A process flow chart of the method for preparing the positive electrode material provided in an embodiment of the present application.

[0018] Figure 2 This is a charge and discharge performance diagram of a battery prepared with the positive electrode materials provided in Example 1 and Comparative Example 1 of the present application.

[0019] Figure 3 The cycle performance diagram of the battery prepared with the positive electrode materials provided in Example 1 and Comparative Example 1 of the present application.

[0020] Figure 4 This is a transmission electron microscope image of the positive electrode material provided in Example 1 of the present application.

[0021] Figure 5 This is a thermogravimetric curve of the positive electrode material provided in Example 1 of the present application in air. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0023] See also Figure 1As shown, the present invention provides a method for preparing a positive electrode material, and the preparation method comprises the following steps: Step S1, pre-treating the carbon nanotubes to obtain open carbon nanotubes.

[0024] In step S1, the carbon nanotubes can be pre-treated by truncation and opening with a nitric acid solution, and the opened carbon nanotubes can be collected and purified by filtration and drying. It can be understood that any method that can pre-treat the carbon nanotubes by truncation and opening includes but is not limited to the above-mentioned nitric acid solution treatment, other acidic solution treatment, oxidizing atmosphere treatment or plasma treatment.

[0025] In some embodiments, the carbon nanotubes may be oriented carbon nanotubes, which are more conducive to the entry of metal salt solutions after vacuuming than disordered carbon nanotubes, and have better mechanical and electrical properties, which are conducive to further improving the stability and electrochemical properties of the positive electrode material. The oriented carbon nanotubes may include at least one of carbon nanotube arrays, oriented multi-walled carbon nanotubes, and oriented double-walled carbon nanotubes.

[0026] In some embodiments, the concentration of the nitric acid solution can be 8 mol / L to 16 mol / L, which is beneficial for pre-treating the carbon nanotubes by shortening and opening. The concentration of the nitric acid solution can further be 10 mol / L to 14 mol / L, and can be 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L, 15 mol / L or 16 mol / L, etc.

[0027] In some embodiments, the ratio of carbon nanotubes to nitric acid solution can be 10 g / L to 50 g / L, which is conducive to further improving the opening effect, and the specific ratio can be further adjusted according to production requirements. The ratio of carbon nanotubes to nitric acid solution can further be 15 g / L to 25 g / L, and can be 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L or 50 g / L, etc.

[0028] In some embodiments, the heating temperature in step S1 can be 130°C to 140°C, which is beneficial to further improve the pretreatment effect and efficiency and accelerate the reaction process of the carbon nanotubes and the nitric acid solution. The heating temperature can further be 135°C to 140°C, and can be 130°C, 132°C, 135°C, 138°C or 140°C, etc.

[0029] In some embodiments, the heating time in step S1 may be 10 h to 12 h, which is beneficial to further improve the pretreatment effect. The heating time may further be 10 h to 11 h, and illustratively may be 10 h, 10.5 h, 11 h, 11.5 h or 12 h.

[0030] In some embodiments, the drying temperature in step S1 can be 60°C to 110°C, which is conducive to further effectively removing impurities and improving the purity of the open carbon nanotubes. The drying temperature can further be 60°C to 90°C, and can be 60°C, 70°C, 80°C, 90°C, 100°C, or 110°C, etc.

[0031] In some embodiments, the drying time in step S1 can be 24 hours to 48 hours, and further can be 24 hours to 36 hours, and illustratively can be 24 hours, 30 hours, 36 hours, 42 hours or 48 hours.

[0032] Step S2, placing the open carbon nanotubes in a container, and evacuating the container to a vacuum degree of 0.05Pa-0.1Pa.

[0033] In this step, the vacuum pumping causes the gas pressure in the container to drop significantly, forming a significant pressure gradient. This pressure difference causes the air and water vapor inside the container to be quickly pumped out, thereby ensuring the cleanliness of the space inside the container. At the same time, the cavity of the open carbon nanotube may also contain gas components, which can be effectively removed by vacuum pumping, providing a near-vacuum environment for the subsequent injection of the metal catalyst solution.

[0034] In some embodiments, the temperature during vacuuming can be 60°C~80°C, which is conducive to further fully discharging the gas inside the open carbon nanotubes, avoiding the formation of bubbles or residual air inside the open carbon nanotubes, so that the catalyst solution in the subsequent steps can fully enter the cavity of the open carbon nanotubes.

[0035] Step S3, maintaining the above vacuum degree, injecting a metal catalyst solution into the container to impregnate the open carbon nanotubes to obtain a precursor mixture.

[0036] In this step, the metal catalyst solution is mixed with the open carbon nanotubes, and the metal catalyst solution can quickly enter the interior of the open carbon nanotubes through the negative pressure liquid phase method. Specifically, under a vacuum state, the pressure difference can effectively promote the metal catalyst solution to quickly penetrate into the interior of the open carbon nanotubes, effectively improving the degree of infiltration of the metal catalyst, which is conducive to the metal catalyst entering the interior of the carbon nanotubes and reducing the amount of metal catalyst used. In addition, the interior of the open carbon nanotubes is a hollow structure, which creates a larger reaction surface area for the reaction of the metal catalyst, so that the metal ions in the metal catalyst solution can effectively contact the inner surface of the carbon nanotubes, and the loading amount of the metal catalyst is increased in a limited space.

[0037] In some embodiments, the metal catalyst solution and the open carbon nanotubes can also be stirred during the impregnation process to ensure uniform dispersion of the solution and allow the metal ions to better combine with the carbon nanotubes, avoid the formation of areas with local excessively high concentrations, and improve the uniformity of dispersion. The stirring time can be 3h to 5h, which is conducive to further improving the impregnation effect and dispersibility of the metal catalyst solution. The time for impregnation and stirring can further be 3h to 5h, and can be exemplarily 3h, 3.5h, 4h, 4.5h or 5h, etc.

[0038] In some embodiments, the metal catalyst solution may include at least one of CoCl2, Co(NO3)2, FeCl3, Fe(NO3)3, NiCl3, Ni(NO3)3, ZnCl2, and Zn(NO3)2. 2+ , Fe 3+ 、Ni 2+ or Zn 2+ Metal ions can further catalyze the reduction / oxidation reaction of sulfur in lithium-sulfur batteries and improve the battery's charge and discharge efficiency; they can also reduce the accumulation of polysulfides on the electrode surface and increase the battery's cycle life; they also help to adsorb lithium polysulfides on carbon nanotubes, reduce their dissolution in the electrolyte, and inhibit the shuttle effect.

[0039] In some embodiments, the concentration of the metal catalyst solution can be 1 g / L to 5 g / L. Since the metal catalyst enters the interior of the open carbon nanotubes, the deactivation caused by direct contact with polysulfides is effectively reduced. Therefore, a lower metal catalyst solution can meet the requirements of efficient catalysis, thereby reducing the amount of catalyst. The concentration of the metal catalyst solution can further be 1 g / L to 3 g / L, and can be 1 g / L, 1.5 g / L, 2 g / L, 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L or 5 g / L, etc.

[0040] In some embodiments, in the precursor mixture, the mass ratio of the metal catalyst solution to the open carbon nanotubes can be (0.1-0.5):1, and a lower content of the metal catalyst solution can meet the requirements of efficient catalysis, which is conducive to cost saving. The mass ratio of the metal catalyst solution to the open carbon nanotubes can further be (0.1-0.3):1, and can be 0.1:1, 0.2:1, 0.3:1, 0.4:1 or 0.5:1, etc.

[0041] In some embodiments, the purity of the carbon nanotubes may be lower than 99%, that is, the purity of the open carbon nanotubes may also be lower than 99%. For example, commercial carbon nanotubes with a purity of less than 99% may be used. Since such materials contain trace amounts of metal catalysts in the production process, they can be used as carbon nanotubes in the embodiments of the present application, which is beneficial to further reduce the use of metal catalysts.

[0042] Step S4, drying and heat treating the precursor mixture to obtain a carbon nanotube composite material.

[0043] In this step, the precursor mixture is filtered and dried to remove external solutions and impurities to obtain a clean solid product. The solid product is then heat-treated to convert metal ions in the metal catalyst solution into metal particles such as metal elements, metal compounds or alloys. The metal particle catalyst is coated inside the carbon nanotubes to obtain a composite material of carbon-coated metal particles.

[0044] Both carbon nanotubes and metal particles have excellent electrical conductivity, and the composite forms a conductive skeleton, which is beneficial to improving the conductivity of the positive electrode material. It is understandable that a small amount of metal particles will also adhere to the outer surface of the carbon nanotubes, which can increase the loading rate of the metal particles. At the same time, due to the small amount, the catalytic efficiency has little effect. The residual metal particles on the surface of the carbon nanotube composite material can also be reduced by further appropriately increasing the number of suction filtration and cleaning.

[0045] Metal catalysts can effectively promote the adsorption of positive electrode materials and the rapid catalytic conversion of polysulfides, thereby reducing the shuttle effect in lithium-sulfur batteries and improving the sulfur utilization rate, thereby improving the coulombic efficiency and cycle life of the prepared lithium-sulfur batteries. At the same time, since the metal particles are coated inside the carbon nanotubes, the risk of direct contact between the metal particles and polysulfides, resulting in the loss of catalytic activity due to sulfurization, can be reduced, which is beneficial to improving the catalytic activity and stability of the metal particles, thereby reducing the shuttle effect of polysulfides, improving the utilization rate of sulfur active substances, and improving the capacity and cycle stability of lithium-sulfur batteries. In addition, the barrier of carbon nanotubes also weakens the strong adsorption of metal particles and polysulfides, releasing the active catalytic sites of the metal catalyst, which is conducive to the efficient and long-lasting catalytic reaction.

[0046] In some embodiments, in step S4, the temperature of the heat treatment may be 400°C to 800°C, which is beneficial to the reduction of metal ions in the metal catalyst solution to form metal particles, and is also beneficial to further promote the crystallization process of the metal particles and improve the particle size and uniformity of the metal particles. The temperature of the heat treatment may further be 600°C to 800°C, and may be 400°C, 500°C, 600°C, 700°C or 800°C, etc.

[0047] In some embodiments, in step S4, the heat treatment time may be 2 h to 3 h, which is beneficial to further improve the crystallization effect of the metal particles. The heat treatment time may further be 2.5 h to 3 h, and may be 2 h, 2.2 h, 2.5 h, 2.6 h, 2.8 h or 3 h, etc.

[0048] In some embodiments, the particle size of the metal particles can be 2nm to 10nm. A smaller particle size is conducive to dispersion inside the carbon nanotubes, while providing a larger specific surface area, further improving the catalytic efficiency. The particle size of the metal particles can further be 2nm to 5nm, and can be 2nm, 3nm, 4nm, 5nm, 7nm, 8nm or 10nm, etc.

[0049] Step S5, adding sulfur to the carbon nanotube composite material, grinding and heating to obtain a positive electrode material.

[0050] Specifically, the carbon nanotube composite material and sulfur are mixed in a mass ratio of (3:7) to (2:8), ground for 30 min to 60 min, and then heat treated at 155°C to 155°C in an inert atmosphere for 10 h to 12 h to obtain a positive electrode material for a lithium-sulfur battery with carbon nanotube-coated metal particles.

[0051] In some embodiments, the commercial carbon nanotubes with a purity lower than 99% in step S3 can also be directly used as the carbon nanotube composite material in the embodiments of the present application, and loaded with sulfur to prepare a positive electrode material, because they contain trace metal catalysts inside.

[0052] Compared with the prior art, the method for preparing the positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. This application uses a negative pressure liquid phase method to fill the metal catalyst solution into the interior of the carbon nanotubes, which reduces the concentration and dosage of the metal catalyst, saves the time of metal catalyst impregnation into the carbon nanotubes, and thus achieves efficient filling at a low metal catalyst dosage. In addition, the metal catalyst content in the positive electrode material is low, which saves production costs while improving catalytic activity and efficiency.

[0053] 2. The structure of the carbon nanotube-coated metal particle catalyst can improve the conductivity of the positive electrode material. At the same time, the catalyst is coated inside the carbon nanotube, which reduces the deactivation caused by direct contact between the catalyst and polysulfide, and can also weaken the strong adsorption of polysulfide, release the active catalytic sites of the catalyst, and ensure a long-term and stable catalytic effect.

[0054] 3. The preparation method of the present application has simple process and low cost, which is conducive to the large-scale production of lithium-sulfur batteries.

[0055] The embodiment of the present application provides a positive electrode material, which is prepared by the above-mentioned preparation method of the positive electrode material. The positive electrode material includes carbon nanotubes, metal particles and sulfur loaded on the carbon nanotubes, wherein the metal particles are located inside the carbon nanotubes, which plays a highly efficient catalytic role, effectively reduces the shuttle effect in the lithium-sulfur battery, and improves the long-term effectiveness and stability of the positive electrode material.

[0056] In some embodiments, in the positive electrode material, the mass percentage of metal particles and open carbon nanotubes can be 1wt%~2.5wt%. A trace amount of metal particle catalyst can achieve long-term and stable operation of lithium-sulfur batteries. The mass percentage of metal particles and carbon nanotubes can further be 1.5wt%~2.5wt%, and can be 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt% or 2.5wt%, etc.

[0057] An embodiment of the present application provides a lithium-sulfur battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet includes the aforementioned positive electrode material.

[0058] Compared with the prior art, the lithium-sulfur battery provided in the embodiment of the present application adopts the aforementioned positive electrode material, which reduces the shuttle effect of polysulfides in the lithium-sulfur battery and effectively improves the capacity, cycle performance and stability of the lithium-sulfur battery.

[0059] The above-mentioned positive electrode material and its preparation method are further described below through specific examples.

[0060] Example 1 Step 1: Dissolve 2 g of carbon nanotube array powder in 100 mL of concentrated nitric acid solution (concentration: 10 mol / L), heat at 140° C. for 10 h, filter and dry at 110° C. for 24 h to obtain open carbon nanotubes.

[0061] Step 2: Place 100 mg of open carbon nanotubes in a round-bottom flask, evacuate for 0.5 h until the vacuum degree reaches 0.1 Pa, and heat in a water bath at 80° C. while evacuating.

[0062] Step 3: Maintain the above vacuum degree, stop heating, and after cooling to room temperature, inject 20 mL of 50 g / L Fe(NO3)3 metal catalyst ethanol solution into the container with a syringe to impregnate the open carbon nanotubes, and stir for 5 hours to obtain a precursor mixture. In addition, in order to maintain the vacuum environment, the syringe is not removed after the liquid is injected.

[0063] Step 4: Rinse and filter the precursor mixture with ethanol, wash off the external solution and dry it to obtain a solid product. The solid product is heat-treated at a rate of 5°C / min to 450°C for 3 hours under an argon atmosphere to obtain a composite material of carbon-coated metal particles with a Fe2O3 content of 2wt%.

[0064] Step 5: uniformly mix the above composite material and sulfur powder in a mass ratio of 3:7, grind for 30 minutes, and keep warm at 155°C for 12 hours in argon protective gas to obtain a positive electrode material in which metal particles Fe2O3 are coated inside carbon nanotubes and the mass percentage of metal particles Fe2O3 and carbon nanotubes is 2wt%.

[0065] Example 2 The specific process of the preparation process refers to Example 1, and the difference from Example 1 is that the temperature of the heat treatment in step 4 is 800°C, and the positive electrode material in which the metal particles Fe3C are coated inside the carbon nanotubes and the mass percentage of the metal particles Fe3C and the carbon nanotubes is 2wt% is obtained. The preparation method of the remaining positive electrode materials is basically the same as that in Example 1, and will not be described in detail here.

[0066] Example 3 The specific process of the preparation process refers to Example 1, and the difference from Example 1 is that the metal catalyst solution in step 3 is a CoCl2 solution; the heat treatment temperature in step 4 is 800°C, and the metal particles Co are coated inside the carbon nanotubes, and the mass percentage of the metal particles Co and the carbon nanotubes is 2wt% of the positive electrode material. The preparation method of the remaining positive electrode materials is basically the same as that in Example 1, and will not be repeated here.

[0067] Comparative Example 1 The specific process of the preparation process refers to Example 1. The difference from Example 1 is that in step 3, no Fe(NO3)3 metal catalyst is added, and only ethanol solution is used for impregnation to obtain a positive electrode material free of metal particles. The preparation method of the remaining positive electrode materials is basically the same as that of Example 1, and will not be described in detail here.

[0068] Comparative Example 2 The specific process of the preparation process refers to Example 1, and the difference from Example 1 is that: no vacuum treatment is performed in step 2, the metal particles Fe2O3 are loaded on the outside of the carbon nanotubes, the metal particles Fe2O3 and the carbon nanotubes have a mass percentage of 2wt% of the positive electrode material, and the preparation method of the remaining positive electrode materials is basically the same as in Example 1, and will not be repeated here.

[0069] The following tests were performed on the positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-2, and corresponding test results were obtained.

[0070] 1. The electrical properties of the positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-2 were tested. The results are shown in Table 1.

[0071] The specific test method is as follows: Electrical performance test: The positive electrode materials in Examples 1-3 and Comparative Examples 1-2 were uniformly mixed with binder PVDF and conductive carbon nanotubes in a mass ratio of 7:2:1 in N-methylpyrrolidone (NMP) solvent, stirred thoroughly to form a slurry, then coated on the current collector, and dried in an oven at 60°C, and finally punched into positive electrode sheets for standby use. The sulfur loading in the positive electrode sheets was 1 mg / cm 2 Next, the button cell was assembled in an argon-filled glove box in the following order: positive electrode shell, gasket, positive electrode sheet, electrolyte, diaphragm, electrolyte, lithium sheet, gasket, shrapnel and negative electrode shell, ensuring that 20 μL / mg electrolyte was added to both sides of the diaphragm. During assembly, the positive electrode shell was at the bottom and the negative electrode shell was at the top, and the lithium-sulfur battery was compacted using a button cell sealer in preparation for testing.

[0072] The test conditions were 25°C, the charge and discharge current was set to 0.5C, the charge and discharge voltage range was 1.7V~2.8V, and 100 cycle tests were performed.

[0073] As can be seen from Table 1, the positive electrode materials of Examples 1-3 all have good first discharge capacity and cycle retention rate. Among them, the cycle retention rate of the positive electrode materials of Examples 1-3 is relatively high, all at 90% and above, with the highest being 93%, which is significantly higher than the cycle retention rates of Comparative Example 1 (70%) and Comparative Example 2 (75%). This shows that the positive electrode materials of carbon nanotube-coated metal particle catalysts prepared by the negative pressure liquid phase method in Examples 1-3 of the present application can significantly improve the cycle performance while maintaining a relatively high first discharge capacity, which is beneficial to improving the longevity and stability of the battery.

[0074] The positive electrode materials prepared in Example 1 and Comparative Example 1 were prepared by referring to the above positive electrode sheet and battery preparation method, and the sulfur loading in the positive electrode sheet was changed to 2 mg / cm 2The electrolyte content is 5μL / mg, and the charge and discharge test is carried out at a discharge current of 0.1C. The results are as follows Figure 2 It shows that when the sulfur loading is 2 mg / cm 2 When the content of the lean electrolyte was 0.03C and the current was 0.03C, the first cycle discharge capacity of the battery prepared in Example 1 was 1350 mAh / g, while that in Comparative Example 1 was only 1230 mAh / g.

[0075] The positive electrode materials prepared in Example 1 and Comparative Example 1 were prepared by referring to the above positive electrode sheet and battery preparation method, and the sulfur loading in the positive electrode sheet was changed to 3.5 mg / cm 2 The electrolyte content is 5μL / mg, and the charge and discharge test is carried out at a discharge current of 0.1C. The results are as follows Figure 3 It shows that under the conditions of high sulfur loading and lean electrolyte, compared with Comparative Example 1, the initial capacity of the battery prepared in Example 1 reaches 900 mAh / g, and can be stably cycled for more than 100 cycles, with excellent specific capacity and cycle performance.

[0076] 2. The positive electrode material obtained in Example 1 was observed by transmission electron microscopy. The results are as follows: Figure 4 As shown, the positive electrode material obtained in Example 1 was subjected to a thermogravimetric test in air, and the results were as follows Figure 5 shown.

[0077] By observation Figure 4 It can be seen that the particle size of the metal particles in Example 1 is about 5 nm, and the metal particles are located inside the carbon nanotube lumen, with good dispersion and uniformity.

[0078] Figure 5 The weight loss peak at 400°C ~ 600°C represents the combustion of carbon (carbon nanotubes) in the air. The results show that the content of metal catalyst in the positive electrode material of Example 1 is 2wt%, which is significantly lower than that of traditional lithium-sulfur positive electrode materials. The high catalytic performance of the positive electrode material is achieved with a lower catalyst content in the examples of the present application, which saves costs and is efficient and stable.

[0079] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a positive electrode material, characterized in that: include: Pre-treating the carbon nanotubes to obtain open carbon nanotubes; Placing the open carbon nanotubes in a container, and evacuating the container to a vacuum degree of 0.05 Pa to 0.1 Pa; Maintaining the vacuum degree, injecting a metal catalyst solution into the container to impregnate the open carbon nanotubes to obtain a precursor mixture; Drying and heat treating the precursor mixture to convert the metal catalyst into metal particles and fill the metal particles inside the open carbon nanotubes to obtain a carbon nanotube composite material; as well as Sulfur is added to the carbon nanotube composite material, and the mixture is ground and heated to obtain the positive electrode material.

2. The method for preparing the positive electrode material according to claim 1, characterized in that: The carbon nanotubes are oriented carbon nanotubes, and the oriented carbon nanotubes include at least one of carbon nanotube arrays, oriented multi-walled carbon nanotubes and oriented double-walled carbon nanotubes; and / or The purity of the carbon nanotubes is lower than 99%.

3. The method for preparing the positive electrode material according to claim 1, characterized in that: The metal catalyst solution comprises at least one of CoCl2, Co(NO3)2, FeCl3, Fe(NO3)3, NiCl3, Ni(NO3)3, ZnCl2 and Zn(NO3)2; and / or The concentration of the metal catalyst solution is 1 g / L to 5 g / L.

4. The method for preparing the positive electrode material according to claim 1, characterized in that: In the precursor mixture, the mass ratio of the metal catalyst solution to the open carbon nanotubes is (0.1-0.5):

1.

5. The method for preparing the positive electrode material according to claim 1, characterized in that: The step of impregnating the open carbon nanotubes with the metal catalyst solution further includes: The metal catalyst solution and the open carbon nanotubes are stirred for 3 hours to 5 hours.

6. The method for preparing the positive electrode material according to claim 1, characterized in that: When the container is evacuated, the temperature inside the container is 60°C to 80°C.

7. The method for preparing the positive electrode material according to claim 1, characterized in that: In the heat treatment step, the heat treatment temperature is 400° C. to 800° C., and the heat treatment time is 3 h to 5 h.

8. A positive electrode material, characterized in that The positive electrode material is prepared by the preparation method of the positive electrode material as described in any one of claims 1 to 7, wherein the positive electrode material comprises a carbon nanotube composite material and sulfur loaded on the carbon nanotube composite material, wherein the carbon nanotube composite material comprises open carbon nanotubes and metal particles located inside the open carbon nanotubes.

9. The positive electrode material according to claim 8, characterized in that In the positive electrode material, the mass percentage of the metal particles and the open carbon nanotubes is 1wt% to 2.5wt%.

10. A lithium-sulfur battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet comprises the positive electrode material as described in any one of claims 8 to 9.

Citation Information

Patent Citations

  • Preparation method of sulfur-silicon carbide doped carbon nano tube material

    CN108598377A

  • Lithium-sulfur battery positive electrode material based on modified carbon nanotubes and preparation method of lithium-sulfur battery positive electrode material

    CN117174877A

  • Display device

    KR1020250001942A

  • Carbon nanotube catalysts having metal catalyst nano-particles supported on inner channel of carbon nanotube and preparation method thereof

    US20100298125A1

  • Cathode active material and cathode comprising metal NANO particles, and lithium-sulfur battery comprising same

    WO2017052246A1